Values in the work of Montessori and traditional teacher. Comparative study. - Karolina Anna Zoszak-Łoskot (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The article presents the results of questionnaire concerned values preferred by teachers working in schools on the basis of traditional and alternative systems - Maria Montessori. The research was conducted in 2017 in the Lublin, Mazovian and Kuyavian-Pomeranian provinces. The S. Schwartz PVQ-RR questionnaire was used in the Polish adaptation of Jan Cieciuch. Overall, the research group of 102 respondents were qualified for the final analysis (Montessori teachers = 51, traditional = 51). In the research undertaken, the aim was to identify values that are valid both by Montessori teachers (research group) and teachers working in the traditional system (comparative group). The collected data presents whether there are differences in the preferred values between the both groups.